Pengaruh Penggunaan Aplikasi Zahir Accounting Terhadap Efisiensi Laporan Keuangan UMKM Toko Material Ehwan 1 - Abiyyu Pangestu; Andreas Soi Hawi; M. Uwais Al Qorni; M. Raihan Basuki; Alifah Nur Maulina (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study attempts to analyze the application usage am zahir accounting for financial efficiency this report on small and medium enterprises, with a case study in a shop material ehwan 1. The background study was left manually recording financial problems that are vulnerable to errors, lost documents, and inefficient in the process of reporting. Methods used is qualitative descriptive by approach case study, through direct observation, interview, and the literature study. The result showed that the accounting version am zahir 6.0 able to increase the accuracy of the transaction, accelerate the preparation of the report, and minimize the miscalculation and loss of data. This program also allows data storage digitally, more secure and easily accessible. The implications of the research suggests that digitalisasi accounting through the use of application am zahir accounting can be effective solutions for small and medium micro businesses to increase efficiency and quality financial decision making. For that reason, it is suggested that technology would adopt similar accounting business to promote sustainability.